KEANEKARAGAMAN LICHEN SEBAGAI BIOINDIKATOR KUALITAS UDARA DI UNIVERSITAS JEMBER - Ardyansyah, Mochammad Aditya Ardyansyah; Audyna, Sayyidha Rahma; Sabrina, Ifa Annisa; Lailiyah, Refi Umairotul; Ambarwati, Dwita; Sari, Intan Suci Novita; Yusana, Erli Viyan; Setiawan, Rendy; Wimbaningrum, Retno (Biosel Biology Science and Education, 2025)
Lichen is an indicator plant that is sensitive to air pollution. This sensitivity is indicated by changes in state, body resistance, and reactions to environmental changes. This study aims to evaluate air quality in the University of Jember environment by using lichen as a bioindicator. The selection of the University of Jember as the research site was based on its unique environmental conditions, namely the presence of high motor vehicle activity, the presence of industry, and also the extent of green areas. Data were obtained through lichen sampling in 15 faculties and analyzed using the Air Quality Index of Atmospheric Purify (IAP). The results showed low average IAP values, indicating poor air quality in the campus environment. The Faculty of Computer Science and Faculty of Agriculture had the lowest IAP values, indicating the highest levels of pollution. Correlations between IAP values and the presence of green spaces and human activity showed that these factors significantly affected air quality. A decrease in lichen diversity indicates an increase in air pollutants, especially from vehicle exhaust. This study concludes that lichens can be an effective tool for monitoring air quality in urban environments, particularly in campus areas. Keyword: Air Quality, Bioindicators, Lichen, Pollution